The operational model of allosteric modulation of pharmacological agonism - Jakubík, Jan; Randáková, Alena; Chetverikov, Nikolai; El-Fakahany, Esam E; Doležal, Vladimír (Scientific reports, 2020)
Proper determination of agonist efficacy is indispensable in the evaluation of agonist selectivity and bias to activation of specific signalling pathways. The operational model (OM) of pharmacological agonism is a useful means for achieving this goal. Allosteric ligands bind to receptors at sites that are distinct from those of endogenous agonists that interact with the orthosteric domain on the receptor. An allosteric modulator and an orthosteric agonist bind simultaneously to the receptor to form a ternary complex, where the allosteric modulator affects the binding affinity and operational efficacy of the agonist. Allosteric modulators are an intensively studied group of receptor ligands because of their selectivity and preservation of physiological space-time pattern of the signals they modulate. We analysed the operational model of allosterically-modulated agonism (OMAM) including modulation by allosteric agonists. Similar to OM, several parameters of OMAM are inter-dependent. We derived equations describing mutual relationships among parameters of the functional response and OMAM. We present a workflow for the robust fitting of OMAM to experimental data using derived equations.
Keywords: alosterická regulace; Protein Binding; synergismus léků; Ligands; Receptors, G-Protein-Coupled; Drug Synergism; Kinetics; Animals; Humans; ligandy; receptory spřažené s G-proteiny; lidé; zvířata; Allosteric Regulation; kinetika; vazba proteinů